2009
DOI: 10.1007/s00586-009-0945-5
|View full text |Cite
|
Sign up to set email alerts
|

Subaxial subluxation after atlantoaxial transarticular screw fixation in rheumatoid patients

Abstract: The most common cervical abnormality associated with rheumatoid arthritis (RA) is atlantoaxial subluxation, and atlantoaxial transarticular screw fixation has proved to be one of the most reliable, stable fixation techniques for treating atlantoaxial subluxation. Following C1-C2 fixation, however, subaxial subluxation reportedly can bring about neurological deterioration and require secondary operative interventions. Rheumatoid patients appear to have a higher risk, but there has been no systematic comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 21 publications
2
35
0
1
Order By: Relevance
“…3 Recent studies stress that in addition to the clinical consequences of cervical malalignment, the geometry of the fusion of the upper cervical spine promotes alignment changes in the subaxial spine. 8,15 Matsunaga et al 14 have observed a higher incidence of subaxial cervical malalignment (kyphosis, swan neck deformity, or subluxation) among patients with occipitocervical fusion in an abnormal position. Yoshimoto el al.…”
mentioning
confidence: 99%
“…3 Recent studies stress that in addition to the clinical consequences of cervical malalignment, the geometry of the fusion of the upper cervical spine promotes alignment changes in the subaxial spine. 8,15 Matsunaga et al 14 have observed a higher incidence of subaxial cervical malalignment (kyphosis, swan neck deformity, or subluxation) among patients with occipitocervical fusion in an abnormal position. Yoshimoto el al.…”
mentioning
confidence: 99%
“…However, the question of whether RA patients are at risk for developing VS and/or SAS after AAS treatment is controversial. Several studies have shown that rheumatoid patients have a greater risk of developing SAS after atlantoaxial fixation using wiring systems or transarticular screws [9][10][11], and the authors emphasized that the risk factor for SAS may be subaxial kyphosis caused by atlantoaxial hyperlordosis. However, the development of SAS is regulated by multiple factors, including not only the mechanical effect of fixed atlantoaxial angle and secondary subaxial kyphosis, but also disruption of the extensor muscles in addition to a strong effect due to a natural history of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported that the incidence of SAS in RA patients not surgically treated was 15-22 % [1,22,23] and of AAS was 18-61 % [1,22]. In patients who were surgically treated, a higher incidence of newly developed SAS and AAS after AA fusion using wiring systems or transarticular screws has been reported (32.7-39 % [9][10][11] and 100 %, respectively). It is suggested that the higher incidence of SAS after the surgery is probably due to mechanical stress caused by changes in cervical alignment, but there is a significant difference in RA status between patients with and without surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA, in particular, is a common cause for such instability, and some authors [5,6,10] have reported their recent clinical results after atlanto-axial arthrodesis. However, idiopathic AAS patients without RA, upper-cervical spine anomaly or any other disorder are rarely encountered.…”
Section: Introductionmentioning
confidence: 99%